Inter Dialytic Weight Gain and Ultrafiltration Goal of Post Covid-19 among Hemodialysis Patients in Riau Province: A Descriptive Study - Bayhakki, Bayhakki; Huda, Nurul; Aziz, Ari Rahmat; Devyna, Yulia; Lai, Claudia. K. Y. (Jurnal Keperawatan Soedirman, 2024)
Key indicators for assessing the adequacy of hemodialysis include Inter-Dialytic Weight Gain (IDWG) and Ultrafiltration Goal (UFG), both of which are closely related to patients' hemodynamic status. However, there is limited information on the specifics of IDWG and UFG, particularly in Riau Province. This quantitative study with a descriptive design aims to describe IDWG and UFG in the aftermath of the COVID-19 pandemic in Riau. The research was conducted across three regional hospitals in Riau Province, involving 138 hemodialysis patients. This study employed univariate statistical analysis, using secondary data as the primary source. The findings indicate that in the first four months following the COVID-19 pandemic among hemodialysis patients in Riau Province, the average UFG and IDWG levels exhibited fluctuations, with IDWG in the three hospitals ranging from 2.28 to 3.12, while UFG was be 2.13 to 3.09. The results suggest that stabilizing of IDWG and UFG is crucial to prevent complications arising from these fluctuations, such as activation of the renin-angiotensin-aldosterone system, stimulation of the sympathetic nervous system, and increased cardiac output.